2001
DOI: 10.1029/2000jd900687
|View full text |Cite
|
Sign up to set email alerts
|

A diagnostic analysis of the Kennedy Space Center LDAR network: 1. Data characteristics

Abstract: Abstract. An analytic framework is developed in which to analyze climatological VHF (66 MHz) radiation measurements taken by the Kennedy Space Center Lightning Detection and Ranging (LDAR) network. A 19 month noise-filtered sample of LDAR observations is examined using this framework. It is found that the climatological impulsive VHF source density as observed by LDAR falls off •10 dB every 71 km of ground range away from the network centroid (a 31 km e-folding scale). The underlying vertical distribution of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 14 publications
(9 reference statements)
6
60
0
Order By: Relevance
“…Eq. (7) indicates that network diameter D controls range uncertainties and confirms the empirical results of Boccippio et al (2001) that range uncertainties increase as r 2 . In addition, the geometry of the network is very important in determining the constant of proportionality of the increase in terms of the basic parameters of the network.…”
Section: Range Determinationsupporting
confidence: 84%
See 1 more Smart Citation
“…Eq. (7) indicates that network diameter D controls range uncertainties and confirms the empirical results of Boccippio et al (2001) that range uncertainties increase as r 2 . In addition, the geometry of the network is very important in determining the constant of proportionality of the increase in terms of the basic parameters of the network.…”
Section: Range Determinationsupporting
confidence: 84%
“…The linearized error estimates are a good approximation to the actual uncertainties. The validity of the covariance error estimates was checked using a Monte Carlo (Twomey, 1977) simulation by Boccippio et al (2001), which showed that the uncertainties were approximated well by the linearized equations and that normally distributed timing uncertainties provide normally distributed positional uncertainties. Koshak et al (2004) compared the linearized covariance error estimates with Monte Carlo simulations and found that both approaches provided similar horizontal errors, but that the linearization approximation gave slightly larger vertical errors for sources outside the network.…”
Section: Calculation Of Location Accuracy Of Networkmentioning
confidence: 99%
“…We used lightning data from the LDAR network developed at NASA Kennedy Space Center (KSC) [ Lennon , 1975; Poehler and Lennon , 1979; Maier et al , 1995; Britt et al , 1998; Boccippio et al , 2000]. LDAR uses time of arrival measurements to locate in three dimensions the impulsive VHF radiation emitted by lightning at a frequency of 66 MHz and a bandwidth of 6 MHz [ McNamara , 2002].…”
Section: Methodsmentioning
confidence: 99%
“…Recently, technology of lightning detecting has been greatly improved on the precision aspect. Based on the technology of LDAR [4], Scientists at New Mexico Institute of Mining and Technology developed a VHF lightning radiation sources locating system by time of arrival tech (LMA) with GPS system, which is used to study the 3D evolution process of the lightning VHF radiation sources [5][6][7]. Using the data of this LMA system, Zhang et al [8][9][10][11] made an analysis showing that the charge structure of thunderstorms often presented a normal triple polarity.…”
mentioning
confidence: 99%